Hearth and home of the Palaeo-Eskimos - Odgaard, Ulla (Études/Inuit/Studies, 2003)
AbstractThis article offers a methodological approach to study hearth features in general. The hearths of the Palaeo-Eskimo tradition are often well preserved, which makes it possible to interpret which heating processes took place, and their effects on the indoor climate of the dwelling. To obtain this type of information, recording of fire-cracked rocks within and in connection to hearths is of special importance. The Palaeo-Eskimos made use of a versatile pyro-technology, adjustable to the most extreme conditions in areas where access to firewood was limited. An archaeological experiment in combination with calculations of hypothetical combustion of fat shows that it was possible for the Independence I people to live through the High Arctic winter in tents with a reasonable degree of comfort. Also, the symbolic aspects of hearths are discussed.